ANALISIS RUKUN DAN SYARAT IJARAH DALAM PEMBIAYAAN MULTIJASA SYARIAH DI BANK SYARIAH - Kusyana, Kusyana; Romlah, Romlah (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2022)
This research delves into the analysis of the pillars and conditions of ijarah in the multi-service financing of Islamic banks. The primary focus is on implementing Sharia principles in ijarah contracts, which includes identifying the pillars of ijarah such as the contracting parties, leased objects, leased benefits, and conditions to be fulfilled such as clarity of leased objects and agreement on rental prices. The study also highlights challenges faced, such as legal uncertainty, regulatory changes, and customer understanding of ijarah contracts. Proposed solutions include enhancing customer education, refining contract documentation, stricter supervision, collaboration with Sharia legal experts, and product innovation. Based on the analysis of the pillars and conditions of ijarah in multi-service financing at Islamic banks, it is concluded that implementing Sharia principles in financial practices is crucial to ensure compliance with Islamic values. The pillars of ijarah involving the contracting parties (mu’jir and musta’jir), leased objects, leased benefits, as well as the ijab and qabul, and ijarah conditions such as clarity of leased objects, permissible benefits, and agreed rental prices, serve as the primary foundation for maintaining fairness and transparency in transactions.